Use of Surface Electromyography to Measure Muscle Fatigue in Patients in an Acute Care Hospital. Issue 6 (11th March 2020) - Skrzat, Julie M; Carp, Stephen J; Dai, Ting; Lauer, Richard; Hiremath, Shivayogi V; Gaeckle, Nathaniel; Tucker, Carole A
Abstract: Background: Functional outcomes with early rehabilitation in the acute care setting have improved; however, an improved understanding of muscle fatigue using surface electromyography (sEMG) is warranted to better guide patient-centered exercise prescription. Objectives: The objectives of this study were to assess the safety and feasibility of collecting sEMG at the acute care bedside and to determine differences in muscle fatigue during isometric and dynamic submaximal contractions among patients in the hospital, healthy younger participants, and healthy older participants. Design: The study used an observational cohort design. Methods: There were 37 participants. Median frequency (Fmed ) of the myoelectric signal of the quadriceps femoris muscles and time to task failure (TTTF) were measured using sEMG during an isometric and dynamic fatiguing contraction. Primary analysis compared TTTF between groups for both types of contractions. Secondary analysis compared Fmed at initiation and termination of fatiguing contraction. Results: High-quality sEMG measures were safe and feasible to collect at the acute care bedside with no adverse events. There was a statistically significant difference in TTTF between groups after isometric and dynamic contractions; hospitalized patients fatigued faster than healthy younger and healthy older participants after both contractions. With the exception of the vastus lateralis during a dynamic contraction in healthy younger and hospitalized patients, there was a statistically significant difference between Fmed at initiation and termination of contraction, indicating that subjects' muscles did truly fatigue. Limitations: A limitation of the study was the small sample size of patients who were hospitalized without matched controls. Conclusions: sEMG is a lab quantitative technique that was found to be safe and feasible to assess muscle fatigue in the acute care environment. The protocol yielded similar results to previously published literature for healthy younger and healthy older people. Further research is needed to better understand how to integrate sEMG findings into patient-centered exercise prescriptions.